The Microbiome, Malignant Fungating Wounds, and Palliative Care - Vardhan, Mridula; Flaminio, Zia; Sapru, Sakshi; Tilley, Charles P.; Fu, Mei R.; Comfort, Christopher; Li, Xin; Saxena, Deepak (Frontiers in Cellular and Infection Microbiology, 2019)
Malignant fungating wounds present in 5% - 14% of advanced cancer patients in the United States and are a result of cancerous cells infiltrating and proliferating in the skin. Presentation of malignant fungating wounds often occurs in the last six months of life and therefore become symbols of impending death for patients and their families. Due to the incurable and severe nature of these wounds, patients require palliative care until death to minimize pain and suffering. Symptoms associated with these chronic wounds include malodor, pain, bleeding, necrosis, large amounts of exudate, increased microbial growth, and more. Limited research using culture-based techniques has been conducted on malignant fungating wounds and therefore no optimal approach to treating these wounds has been established. Despite limited data, associations between the cutaneous microbiome of these wounds and severity of symptoms have been made. The presence of at least one strain of obligate anaerobic bacteria is linked with severe odor and exudate. A concentration of over 105/g bacteria is linked with increased pain and exudate. Bacterial metabolites such as DMTS and putrescine are linked with components of malignant fungating wound odor and degradation of periwound skin. The few but significant associations made between the malignant fungating wound microbiome and severity of symptoms indicate that further study on this topic using 16S rRNA gene sequencing may reveal potential therapeutic targets within the microbiome to significantly improve current methods of treatment used in the palliative care approach.